The Association of Fasting C-peptide with Corneal Neuropathy in Patients with Type 2 Diabetes - Anju Zuo; Chuan Wang; Lili Li; Jingru Qu; Juan Cao; Li Chen; Solomon Tesfaye; Wenjuan Li; Xinguo Hou (Journal of Diabetes Research)
Purpose. Damage to corneal nerve fibers has been demonstrated in people with type 2 diabetes mellitus (T2DM) that further progresses with increasing severity of diabetic peripheral neuropathy. However, the role of C-peptide in corneal nerve damage has not been reported in T2DM. The present study investigated the relationship of fasting C-peptide levels with corneal neuropathy evaluated by corneal confocal microscopy (CCM) in patients with T2DM. Methods. 160 T2DM patients (72 females) aged 34-78 with duration ranging from 0 to 40 years underwent CCM to measure corneal nerve fiber length (CNFL), corneal nerve fiber density (CNFD), and corneal nerve branch density (CNBD). Pearson correlation analysis and multiple linear regression analysis were used to explore the association of fasting C-peptide levels with corneal nerve parameters. Partial correlation analysis (adjusted for age and gender) was also conducted to analyze the correlation of metabolic indexes with these three corneal nerve parameters. The relationship between fasting C-peptide levels and duration of diabetes was also explored by Pearson correlation analysis. Results. With an increase in fasting C-peptide levels, the values of CNFL, CNFD, and CNBD also showed a corresponding trend for an increase. Partial correlation analysis revealed that fasting C-peptide levels were positively associated with CNFL (r=0.245, P=0.002), CNFD (r=0.180, P=0.024), and CNBD (r=0.214, P=0.008) after adjusting for age and gender. Using multiple linear regression analysis, fasting C-peptide levels were also closely associated with CNFL (P=0.047) and CNBD (P=0.038) after multiple adjustments. However, this association disappeared after further adjusting for duration of diabetes. Further analysis indicated that fasting C-peptide levels declined with duration of diabetes (r=−0.267, P=0.001). Conclusions. C-peptide was closely associated with corneal neuropathy and disease duration in T2DM. C-peptide levels might be both an indicator of beta-cell function and a marker of disease severity (such as diabetic corneal neuropathy) and duration.